Selective impact of COVID-19 in patients presenting with non-specific abdominal pain. Issue 4 (1st April 2021) - Alsaoudi, T; Slavin, D; Khasawneh, F; Chung, W Y; Eltweri, A; Sahloul, M; Bhardwaj, N; Malde, D; Dennison, A R; Garcea, G
Abstract : The effect of COVID on surgical admissions was investigated by comparing such admissions from March to August 2020 with those in the same period in 2019. A significant reduction was noted in surgical admissions. The majority of this reduction was seen in the group with non-specific abdominal pain. It is presumed that public adherence to authorities' message and effective ambulatory care are behind this decrease. we investigated the COVID effect on surgical admissions by comparing surgical admissions to the same period in 2019. significant reduction was noted of surgical admissions. interestingly, the majority of this reduction was seen in the non specific abdominal pain group. it is presumed that public adherence to authorities message and effective ambulatory care are behind this decrease.